Prediction of Local Scour Rate around Bridge Piers Using SSIIM Model - Abdeldayem, Ahmad W.; Elsaeed, Gamal H.; Toukhy, Mahmoud A.R. El; Ghareeb, Ahmed A. (IJRDO-Journal of Applied Science, 2015)
Scouring around bridge piers phenomena are studied by several researchers. They proved that SSIIM (Sediment Simulation In Intakes with Multi-block option) model is a powerful tool in predicting local scour around rectangular piers for clear water scour. The main objective of this paper is to verify SSIIM model in predicting the local scour for live bed and clear water scour around bridge piers. Also, it covered prediction of scour for circular and rectangular piers with different sizes. In addition the predicted scour rate was compared with the scour rate obtained from experimental results by Sharafaddin A.A.S. (2003). All results were represented in curves. These curves showed good agreement between the predicted values by SSIIM and the experimental results. Moreover, the final scour values were in a good agreement with the values calculated by the most famous scour equation.